Clinical evaluation of panchavalkal kashay dhavan In the management of diabetic wound: Array - Sonekar, Aruna; More, Yogesh B.; Sonekar, Rajendra (Ayurline: International Journal of Research in Indian Medicine, 2016)
The ingredients of Panchavalkala has the properties of kaphavatahara and also varnya and vrana ropana, rakta shodhaka properties hence by administering these drugs in the form of Kashaya, it will clear the ducts and also does the varna prasadana. The drugs in this Kashaya are also having anti inflammatory effect, thus help in treating diabetic wound. Because Panchavalkala Kashaya seems to have property like Vranaprakshalana, Vranaropana and Shothahara. Preventing secondary infections in the Diabetic Wounds with safe and efficacious anti bacterial agents is must in the current scenario to enhance the wound healing process. Panchavalkala has activities like vranaprakshalana, vranaropana, shothahara, upadanshahara, visarpahara. Study revealed that Panchavalkala kwatha is kapha shamaka, stambhaka and having the properties like astringent, antiseptic (kashaya rasa) and wound healing (vrana ropana). Because of these properties it helps in increasing local cell immunity and prevents recurrence of symptoms in patients